Silicon-substituted olefin catalyst as well as preparation method and application thereof
By providing a silicon-substituted olefin catalyst, the problem of lack of effective catalysts for the polymerization of silicones and olefins in the prior art is solved, and the preparation of high molecular weight silicones olefin copolymers is achieved, and excellent curing properties are demonstrated.
Patent Information
- Application Number
- CN202411873157.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-11
AI Technical Summary
There is a lack of effective catalysts for polymerization of silicones and olefins, especially the preparation of high molecular weight silicones olefin copolymers.
A silicon-substituted olefin catalyst is provided with a structure of a combination of a transition metal complex zirconium, titanium or platinum chloride with a specific cyclopentadiene salt and chlorosilane, and the catalyst is prepared by a specific preparation method.
This catalyst can effectively catalyze the polymerization of ethylene and propylene, improve the molecular weight and monodispersity of the polymer, and has excellent curing depth, and is suitable for thermal curing or photocuring.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalysts, and in particular to a silicon-substituted olefin catalyst and a preparation method and application thereof. Background Art
[0002] In the prior art, various precursors are usually used and various polymerization techniques are used to optimize the preparation of silylene polymers. Silylene is a class of compounds containing silicon-olefin bonds, which can be used as monomers to prepare silylene polymers in polymerization reactions. In the polymerization reaction of silylene, it is usually necessary to use a specific catalyst to promote the reaction. These catalysts can usually be metal catalysts or organic catalysts. At present, the application of organic catalysts is also gradually increasing. For example, nitrides, alkali metal salts, etc. can play a catalytic role in the polymerization of silylene. The selection of these catalysts depends on the specific structure of silylene, the reaction characteristics of the monomers, and the desired properties of the polymerized product.
[0003] For example, Ziegler-Natta catalysts can control the stereostructure of polymer chains, especially in propylene polymerization, and can accurately synthesize isotactic, syndiotactic or atactic polypropylene. This control ability is critical for obtaining polymers with specific physical properties; titanium-based catalysts can not only catalyze the polymerization of ethylene and propylene, but also catalyze the polymerization of other α-olefins, such as 1-butene, 1-hexene, etc., to form different types of polymers. The Ziegler-Natta catalyst system has high catalytic activity and can carry out polymerization reactions under lower temperature and pressure conditions, thereby improving production efficiency. In addition to the above-mentioned commonly used silylene polymerization catalysts, many other types of catalysts are also used for the polymerization of silylene, such as iron catalysts, palladium catalysts, etc., which can promote the polymerization of silylene under specific conditions, and directly introduce silicon groups into traditional olefin monomers or polymers through silylene reactions. The latest research has made progress in the selectivity, efficiency and development of catalysts for the reaction. In particular, the desired properties can be obtained by finely controlling the position and number of silicon groups.
[0004] In the case of olefin free radical polymerization, usually a transition metal catalyst, such as a ferrocene catalyst, is used to initiate the free radical polymerization of silylene. Palladium catalysts are also commonly used in the polymerization of silylene, especially the cross-linking polymerization of silylene and silyl monomers. The olefin polymerization using metallocene or post-metallocene catalysts is well known. For example, publication number is in the international patent application WO 2005090418A1, describing that cyclopentadienylamide catalysts can produce high molecular weight ethylene / alpha-olefin copolymers. However, there is still a need to further develop new catalysts for siloxane and olefin polymerization, particularly for the preparation of high molecular weight siloxane olefin copolymers. Summary of the invention
[0005] In order to solve the above technical problems, one of the objects of the present invention is to provide a silicon-substituted olefin catalyst for ethylene polymerization, propylene polymerization and preparation of siloxane olefins, and the polymer has a high molecular weight; the second object of the present invention is to provide a method for preparing the above silicon-substituted olefin polymerization catalyst; the third object of the present invention is to provide an application of the above silicon-substituted olefin polymerization catalyst.
[0006] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0007] A silicon-substituted olefin polymerization catalyst is shown in the following structural formula (1):
[0008]
[0009] In the formula, M is a chloride of a transition metal complex of zirconium, titanium or platinum; R1, R2, R3, R4 and R5 are each independently a hydrogen atom, a trimethylsilyl group, an aromatic hydrocarbon group or a straight or branched alkyl group having 1 to 20 carbon atoms; R6, R7 and R8 may be the same or different and represent a hydrogen atom, a halogen atom or an alkoxy group.
[0010] A method for preparing the silicon-substituted olefin catalyst as described above comprises the following steps:
[0011] (1) Preparation: In a protective atmosphere, in an anhydrous and oxygen-free environment, a transition metal precursor is obtained by dropwise adding a Grignard reagent alkali metal salt to a mixture of a transition metal halide, an ether reagent and a Lewis acid;
[0012] (2) In the presence of magnesium halide, a specific cyclopentadienyl salt is reacted with a transition metal precursor to obtain a cyclopentadienyl compound A; and then the compound A is added dropwise to a mixed solution of chlorosilane and tetrahydrofuran in a certain proportion to obtain a silicon-substituted olefin polymerization catalyst.
[0013] Preferably, the Grignard reagent alkali metal salt is one or more of methylmagnesium halide, ethylferric halide, methylaluminoxane, ethylaluminoxane, isobutylaluminoxane and butylaluminoxane.
[0014] Preferably, the magnesium halide is magnesium chloride.
[0015] Preferably, the ether solvent is diethyl ether, tetrahydrofuran or tert-butyl methyl ether.
[0016] Preferably, the Lewis acid is one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum and ethyldimethylaluminum.
[0017] Preferably, the specific cyclopentadienyl salt is one or more of cyclopentadienyl monohalogenated dialkylsilane, cyclopentadienyl-containing monohalogenated dialkylsilane, cyclopentadienyl-containing monohalogenated diarylsilane, cyclopentadienyl magnesium and cyclopentadienyl sodium.
[0018] Preferably, the cyclopentadienyl compound A is represented by the following structural formula (2):
[0019]
[0020] Wherein X is zirconium, titanium or platinum; Y is a monohalogenated dialkylsilane containing a cyclopentadienyl group.
[0021] Preferably, in step (2), the ratio of chlorosilane to tetrahydrofuran is 1:2-1:6.
[0022] An application of the silicon-substituted olefin catalyst as described above, wherein the silicon-substituted olefin catalyst is used for olefin polymerization or organosiloxane polymerization.
[0023] The present invention has the following beneficial effects due to the adoption of the above technical solution:
[0024] 1. The silicon-substituted olefin catalyst provided in this scheme can be used for various synthetic resins, has a catalytic polymerization effect on ethylene and propylene, and provides the molecular weight and monodispersity of ethylene polymers and propylene polymers; the silicon-substituted olefin catalyst can also provide active centers and cure silicone resins by thermal curing or photocuring, catalyze siloxane polymerization, and has excellent curing depth; the present invention can also be used as a raw material for synthesizing various new functional silane compounds, because different types of functional groups can be introduced into the cyclopentadienyl contained in the molecule of the compound of the present invention through the Diels-Alder reaction; the silicon-substituted olefin catalyst can also serve as an important intermediate in the metal-catalyzed coupling reaction, reacting with the metal catalyst through the boron group or other substituent group to generate a new carbon-silicon bond or carbon-carbon bond, participating in the coupling reaction, and can also form a carbon-silicon bond or other chemical bond through an oxidation-reduction reaction, and a cross-linking polymerization reaction of silicon olefins and silane monomers, thereby playing a key role in organic synthesis.
[0025] 2. In the preparation process of the silicon-substituted olefin catalyst, the alkali metal salt is reacted with the halogenated silane or the halogenated hydrocarbon, and the side reaction caused by the alkali metal-hydrogen exchange is suppressed, so that the hydrocarbon compound containing cyclopentadienyl group or the silicon-substituted olefin catalyst containing cyclopentadienyl group can be synthesized at a high speed. The production method of the present invention can reliably produce a new type of cyclopentadienyl group-containing silane compound with a simple process by using easily available raw materials. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] Embodiment 1:
[0028] 1. Equipped with a thermometer, a stirring device and a condenser. The interior of a 500 ml glass reactor is fully purified and filled with nitrogen in advance. Then, 54.4 titanium tetrachloride (TiCl4) is mixed with triethylaluminum (Al(C2H5)3) to prepare a titanium-based catalyst. The catalyst is pre-activated to obtain a tetrahydrofuran solution with high activity titanium chloride, followed by 6.7 g of ethyl sodium iodide and lithium bromide dissolved in tetrahydrofuran (5.5 ml) added to the reactor, and the mixture is cooled with water and stirred for 13 to 30 minutes while maintaining the reaction temperature. Within a temperature range of 25°C, 8.5 g of magnesium chloride in ether and 12.8 g of 2.0 mol / l cyclopentadienylchlorodimethylsilane in tetrahydrofuran (THF) are added dropwise to the above container over 0.5 hours and stirred overnight at room temperature.
[0029] 2. 124.2 g of 2-(trimethylsilylmethyl)-2-propene-1-ol and a tetrahydrofuran solution of trichlorosilane were added dropwise respectively; as the mixture was added, heat was generated and fine yellow-brown crystals were precipitated. Next, the temperature of the solution was raised and the solution was aged at 74° C. for 24 hours under THF reflux. Afterwards, 10 ml of water was added while cooling in an ice-water bath to quench the unreacted cyclopentadienyl sodium, and the solution was washed once with water. The mixture was then dehydrated with magnesium sulfate, THF was distilled off from the liquid using an evaporator, and then distilled under reduced pressure to obtain a compound cyclopentadienyl [2-(trimethylsilylmethyl) allyl titanium with a boiling point of 68° C., i.e., a silicon-substituted olefin catalyst.
[0030] 3. In the reactor, evacuate and replace with nitrogen to remove air. Clean and dry the autoclave to ensure that there is no moisture and impurities. Add 100 mL of n-hexane (C6H 14), 0.865 μmol cyclopentadienyl [2- (trimethylsilylmethyl) allyl titanium and ensure complete dissolution. Introduction of gas: Remove the air in the reactor by vacuuming and replacing it with nitrogen. Under an inert atmosphere, slowly introduce ethylene gas, adjust to the required reaction pressure of 2MPa, set the reaction temperature to 70°C, keep the reaction pressure stable at 2MPa, and during the reaction, ensure that the agitator works normally to ensure uniform reaction. Allow the reaction to proceed for 4 hours. During this period, monitor the reaction temperature and pressure regularly to ensure that they remain within the set range. During the reaction, the consumption of ethylene can be monitored by a gas flow meter. After the reaction reaches the set time, the introduction of ethylene is stopped and the reaction pressure is reduced to normal pressure. Gradually add about 5 mL of isopropanol as a terminator to ensure that the reaction is completely stopped. Polyethylene is separated from the reaction mixture by precipitation. The reaction mixture can be poured into a large amount of ethanol, and the polyethylene will precipitate. The precipitated polyethylene is separated using a filter and washed several times with ethanol to remove unreacted monomers and catalyst residues. The washed polyethylene was placed in a vacuum oven at 60° C. and dried for 24 hours to remove the solvent to obtain polymer 1.
[0031] Embodiment 2:
[0032] 1. Equipped with a thermometer, a stirring device and a condenser. The interior of a 500 ml glass reactor was fully purified and filled with nitrogen in advance. Then, 63.2 g of a solution of platinum chloride in ether, 6.7 g of isobutylaluminoxane and 0.8 g of trimethylaluminum were added to the reactor, and the mixture was cooled with water and stirred for 13 to 30 minutes while maintaining the reaction temperature. Within a temperature range of 25° C., 8.5 g of a solution of magnesium chloride in tetrahydrofuran and 12.8 g of 2.0 mol / l cyclopentadienyl magnesium in tetrahydrofuran (THF) were added dropwise to the above container over 0.5 hours and stirred overnight at room temperature.
[0033] 2. Add 92.7 g of chlorotris(trimethylsiloxy)silane and trichlorosilane in tetrahydrofuran respectively; heat is generated as the mixture is added, and fine yellow-brown crystals are precipitated. Next, the temperature of the solution is increased, and the solution is aged at 82°C for 24 hours under THF reflux. After that, 10 ml of water is added while cooling in an ice-water bath to quench the unreacted cyclopentadienyl sodium, and the solution is washed with water once. 0.73 g (30.0 mmol) of magnesium flakes are loaded into a 200 mL reactor that has been fully dried and purged with argon, and heated under reduced pressure while vigorously stirring for 30 minutes. After cooling to room temperature, a reflux condenser is installed, and iodine flakes and 20 mL of tetrahydrofuran are added and stirred. After the reaction is completed by dripping a diluted solution of 2.93 g (15.0 mmol) of 2-bromoindene in 20 mL of tetrahydrofuran, the mixture is stirred for 1 hour under heating reflux. After the reaction solution was cooled to room temperature, it was slowly added to a dilute solution of 9.00 mL (75.0 mmol) of dimethyldichlorosilane in 15 mL of n-hexane under cooling at -78°C, and stirring was continued for 22 hours while the solution was returned to room temperature. After the solvent and unreacted dimethylsilyl dichloride of the reaction solution were distilled off, 10 mL of tetrahydrofuran was added to the residue, and the resulting diluted reaction residue solution was cooled to -78°C again.
[0034] 3. Place 2.28 mL (15.0 mmol) of 1,2,3,4-tetramethyl-1,3-cyclopentadiene and 15 mL of tetrahydrofuran in a 100 mL reactor that has been thoroughly dried and purged with argon. Add 9.88 mL of 1.60 M, 15.8 mmol hexane solution to dissolve and stir at room temperature for 2 hours, then add 3.24 mL (30.0 mmol) of 1,3-dimethyl-2-imidazolidinone and stir until clear to obtain a solution. Add the solution dropwise to the diluted solution of the reaction residue cooled to -78°C, and continue stirring for 20 hours while slowly returning to room temperature. Add saturated aqueous ammonium chloride solution, extract the soluble components with ethyl acetate, wash with saturated brine, and dry over anhydrous magnesium sulfate. After filtering magnesium sulfate, the filtrate was distilled off, the obtained residue was purified by silica gel column chromatography, and then the mixture was dehydrated with sodium sulfate. THF was distilled off from the liquid using an evaporator, and then distilled under reduced pressure to obtain a compound 1,3-diphenyl-cyclopentadienyl platinum tris(trimethylsiloxy)silane with a boiling point of 68°C, that is, a silicon-substituted olefin catalyst.
[0035] 4. Mix 95g of divinyl polydimethylsiloxane with a polymerization degree of 500 and 0.002g of 1,3-diphenyl-cyclopentadienyl platinum tris(trimethylsiloxy)silane, 12g of polyamide wax powder, and 1.6g of hydroxymethyl cellulose to obtain component A; mix 75g of divinyl polydimethylsiloxane with a viscosity of 1000 polymerization degree, 8.2g of terminal methyl side hydrogen silicone oil, 3g of terminal hydrogen silicone oil, 1.5g of polyethylene glycol with a molecular weight of 2000, 102g of spherical aluminum nitride, and 0.0003g of ethynyl cyclohexanol to obtain component B; then mix 50g of A glue and 25g of The B glue was mixed and stirred at a temperature of 30°C and a speed of 20 r / min for 1.5 hours, and then mixed and stirred with the mixed material at a temperature of 30°C and a speed of 20 r / min for 1.5 hours, and then degassed in a vacuum environment for 5 minutes and cured at a temperature of 120°C to obtain polymer 2.
[0036] Embodiment 3:
[0037] 1. Equipped with a thermometer, a stirring device and a condenser. The interior of a 500 ml glass reactor was fully purified and filled with nitrogen in advance. Then, 63.2 g of a solution of platinum chloride in ether, 6.7 g of isobutylaluminoxane and 0.8 g of trimethylaluminum were added to the reactor, and the mixture was cooled with water and stirred for 13 to 30 minutes while maintaining the reaction temperature. Within a temperature range of 25° C., 8.5 g of a solution of magnesium chloride in tetrahydrofuran and 12.8 g of 2.0 mol / l cyclopentadienyl magnesium in tetrahydrofuran (THF) were added dropwise to the above container over 0.5 hours and stirred overnight at room temperature.
[0038] 2. Add 92.7 g of chlorotris(trimethylsiloxy)silane and trichlorosilane in tetrahydrofuran respectively; heat is generated as the mixture is added, and fine yellow-brown crystals are precipitated. Next, the temperature of the solution is increased, and the solution is aged at 82°C for 24 hours under THF reflux. After that, 10 ml of water is added while cooling in an ice-water bath to quench the unreacted cyclopentadienyl sodium, and the solution is washed with water once. 0.73 g (30.0 mmol) of magnesium flakes are loaded into a 200 mL reactor that has been fully dried and purged with argon, and heated under reduced pressure while vigorously stirring for 30 minutes. After cooling to room temperature, a reflux condenser is installed, and iodine flakes and 20 mL of tetrahydrofuran are added and stirred. After the reaction is completed by dripping a diluted solution of 2.93 g (15.0 mmol) of 2-bromoindene in 20 mL of tetrahydrofuran, the mixture is stirred for 1 hour under heating reflux. After the reaction solution was cooled to room temperature, it was slowly added to a dilute solution of 9.00 mL (75.0 mmol) of dimethyldichlorosilane in 15 mL of n-hexane under cooling at -78°C, and stirring was continued for 22 hours while the solution was returned to room temperature. After the solvent and unreacted dimethylsilyl dichloride of the reaction solution were distilled off, 10 mL of tetrahydrofuran was added to the residue, and the resulting diluted reaction residue solution was cooled to -78°C again.
[0039] 3. Place 2.28 mL (15.0 mmol) of 1,2,3,4-tetramethyl-1,3-cyclopentadiene and 15 mL of tetrahydrofuran in a 100 mL reactor that has been thoroughly dried and purged with argon. Add 9.88 mL of 1.60 M, 15.8 mmol of n-hexane solution to dissolve and stir at room temperature for 2 hours, then add 3.24 mL (30.0 mmol) of 1,3-dimethyl-2-imidazolidinone and stir until clear. Obtain a solution. Add the solution dropwise to the diluted solution of the reaction residue cooled to -78°C, and continue stirring for 20 hours while slowly returning to room temperature. Add saturated aqueous ammonium chloride solution, extract the soluble components with ethyl acetate, wash with saturated brine, and dry with anhydrous magnesium sulfate. After filtering magnesium sulfate, the filtrate was distilled off, the obtained residue was purified by silica gel column chromatography, and then the mixture was dehydrated with sodium sulfate. THF was distilled off from the liquid using an evaporator, and then distilled under reduced pressure to obtain a compound 1,3-diphenyl-cyclopentadienyl platinum tris(trimethylsiloxy)silane with a boiling point of 68°C, that is, a silicon-substituted olefin catalyst.
[0040] 4. Under nitrogen atmosphere, 500 mL of heptane was added to a 1 L SUS autoclave equipped with a stirring blade and fully purged with nitrogen, toluene was added to a 500 mL glass reactor fully replaced with nitrogen, 10 mL of vinyltrimethoxysilane was slowly added to the reactor, stirred evenly, and ethylene and 100 L of water were introduced at a rate of 100 L / h. Propylene was added to saturate the liquid phase and the gas phase. Then, triisobutylaluminum was added to 0.2 mmol in terms of aluminum atoms, the compound 1,3-diphenyl-cyclopentadienyl platinum tris(trimethylsiloxy)silane was added to 0.0625 μmol, and then triphenylcarbonium tetra(petroleum) was added. Polymerization was started by adding 0.25 μmol of fluorophenyl borate. Ethylene was continuously supplied at 100 L / h, propylene was continuously supplied at 100 L / h, and polymerization was carried out at normal pressure and an internal temperature of 50°C for 10 minutes, and then a small amount of propylene was added to stop the polymerization. After the polymerization was completed, the toluene solution containing the polymer was transferred to a separatory funnel. An aqueous hydrochloric acid solution was prepared by adding 2 mL of concentrated hydrochloric acid to 200 mL of water, and the solution was added to a separatory funnel to wash the organic layer and separate the organic layer and the aqueous layer. The organic layer was washed again with an aqueous hydrochloric acid solution and then washed with 200 mL of distilled water to separate the organic layer and the aqueous layer. The organic layer was concentrated using a rotary evaporator, and the obtained polymer was dried under reduced pressure at 80°C for 10 hours to obtain a pure silicon-modified propylene polymer, i.e., polymer 3.
[0041] Comparative Example 1:
[0042] The difference from Example 1 is that after the liquid phase and the gas phase are saturated with ethylene, an equimolar amount of a metallocene catalyst dicyclopentadienyl titanium dichloride and a co-catalyst methylaluminoxane are added to replace the cyclopentadienyl [2-(trimethylsilylmethyl)allyl titanium in Example 1 to polymerize ethylene to obtain polymer 4.
[0043] Comparative Example 2:
[0044] The difference from Example 2 is that the compound 1,3-diphenyl-cyclopentadienylplatinum tris(trimethylsiloxy)silane is replaced by an equal molar amount of bis(1,3-divinyl-1,1,3,3-tetramethyldisiloxane)platinum-KARSTEDT catalyst, and divinyl polydimethylsiloxane is polymerized to obtain polymer 5.
[0045] Comparative Example 3
[0046] The difference from Example 3 is that 1,3-diphenyl-cyclopentadienyl platinum tris(trimethylsiloxy)silane is replaced by a mixed cyclohexane solution of triethylaluminum (Al(C2H5)3) and titanium tetrachloride (TiCl4) in equal molar amounts, and silicon-modified propylene is polymerized to obtain polymer 6.
[0047] Methods for measuring polymer physical properties:
[0048] 1. Measurement methods of number average molecular weight (Mn), weight average molecular weight (Mw), and molecular weight distribution (Mw / Mn):
[0049] Agilent 1260 Infinity GPC system with GPC-viscosity detector manufactured by Agilent was used, equipped with a differential refractive index detector (RI Detector), two Agilent PLgel Olexis were used as analytical columns, high purity tetrahydrofuran (THF), HPLC grade, was used as mobile phase, the flow rate was 1.0 ml / min, and the sample concentration was 0.1 wt %. A polystyrene (PS) standard sample series was used for calibration (molecular weight range from 500 g / mol to 500,000 g / mol). When calculating the molecular weight, the measured viscosity was calculated using a viscometer and a refractometer, and the number average molecular weight (Mn), weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) were obtained from the measured values.
[0050] 2. Storage modulus is tested according to ASTM E2254-18 standard test method for calibration of storage modulus of dynamic mechanical analyzer;
[0051] 3. The light curing test method is at a wavelength of 365nm and an energy of 20000mj / cm 2 To evaluate whether it can be cured under ultraviolet light:
[0052] 4. The wear resistance test method is in accordance with the requirements of GB / T 3960-2008 "Plastic Sliding Friction and Wear Test Methods":
[0053] The curing performance of the polymers prepared by the catalysts in Examples 1-3 and Comparative Examples 1-3 was tested according to the above method. The test results are shown in Table 1 below:
[0054] Table 1: Curing properties of polymers catalyzed in Examples 1 to 3 and Comparative Examples 1 to 3
[0055]
[0056] According to Table 1, Comparative Examples 1 and 3 respectively use metallocene catalysts and Ziegler-Natta catalysts to catalyze the polymerization of ethylene and propylene, respectively. Examples 1 and 3 use silicon-substituted olefin catalysts, which have catalytic effects on both polymers and have corresponding improvements in molecular weight and monodispersity. Example 2 and Comparative Example 2 use silicon-substituted olefin catalysts and commercially available KARSTEDT catalysts, respectively. The results show that silicon-substituted olefin catalysts have a photocuring effect on organosilicon polymers, and the curing depth is higher. As described in detail above, the cyclopentadienyl-silane-containing compound of the present invention can be used for various synthetic resins, especially it has excellent deep curing properties, and can provide active centers to cure organosilicon compositions, whether by thermal curing or photocuring.
[0057] Moreover, the silicon-substituted olefin catalyst can be used as a precursor molecule for CVD to deposit silicon-substituted films by thermal decomposition or photolysis. For example, silicon-substituted cyclopentadiene derivatives can be thermally decomposed in a vacuum to form silicon-substituted films on the surface. Such films can be used as protective layers, thermal insulation layers or other functional films and can be used in optical films, electronic devices, photovoltaic materials and other fields.
[0058] All features described in the description and the appended claims are essential features of the invention both individually and in any combination.
[0059] Although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. Ordinary technicians in the field can change, modify, replace, modify, delete some features, add features or re-combine features to form a technical solution in the above embodiments without departing from the principles and purpose of the present invention. Any simple modifications, equivalent changes and modifications made to the above embodiments based on the innovative principles of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A silicon-substituted olefin polymerization catalyst, characterized in that: As shown in the following structural formula (1): In the formula, M is a chloride of a transition metal complex of zirconium, titanium or platinum; R1, R2, R3, R4 and R5 are each independently a hydrogen atom, a trimethylsilyl group, an aromatic hydrocarbon group or a straight or branched alkyl group having 1 to 20 carbon atoms; R6, R7 and R8 may be the same or different and represent a hydrogen atom, a halogen atom or an alkoxy group.
2. A method for preparing a silicon-substituted olefin catalyst as claimed in claim 1, characterized in that: The following steps are involved: (1) Preparation: In a protective atmosphere, in an anhydrous and oxygen-free environment, a transition metal precursor is obtained by dropwise adding a Grignard reagent alkali metal salt to a mixture of a transition metal halide, an ether reagent and a Lewis acid; (2) In the presence of magnesium halide, a specific cyclopentadienyl salt is reacted with a transition metal precursor to obtain a cyclopentadienyl compound A; and then the compound A is added dropwise to a mixed solution of chlorosilane and tetrahydrofuran in a certain proportion to obtain a silicon-substituted olefin polymerization catalyst.
3. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The alkali metal salt of the Grignard reagent is one or more of methyl magnesium halide, ethyl iron halide, methyl aluminoxane, ethyl aluminoxane, isobutyl aluminoxane and butyl aluminoxane.
4. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The magnesium halide is magnesium chloride.
5. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The ether solvent is diethyl ether, tetrahydrofuran or tert-butyl methyl ether.
6. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The Lewis acid is one or more of trimethylaluminum, triethylaluminum, triisobutylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum and ethyldimethylaluminum.
7. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The specific cyclopentadienyl salt is one or more of cyclopentadienyl monohalogenated dialkylsilane, cyclopentadienyl-containing monohalogenated dialkylsilane, cyclopentadienyl-containing monohalogenated diarylsilane, cyclopentadienyl magnesium and cyclopentadienyl sodium.
8. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: The cyclopentadienyl compound A is represented by the following structural formula (2): Wherein X is zirconium, titanium or platinum; Y is a monohalogenated dialkylsilane containing a cyclopentadienyl group.
9. The method for preparing a silicon-substituted olefin catalyst according to claim 2, characterized in that: In step (2), the ratio of chlorosilane to tetrahydrofuran is 1:2-1:
6.
10. Use of the silicon-substituted olefin catalyst according to claim 1, characterized in that: The silicon-substituted olefin catalyst is used for olefin polymerization or organosiloxane polymerization.
Citation Information
Patent Citations
Polimerization catalyst comprising an amidine ligand
WO2005090418A1